Gestão do conhecimento para desenvolvimento de novos produtos: um estudo de caso na agroindústria de carnes de aves no Paraná - Brambilla, Norma (2008)
The study has for target to identify the contribution of the Knowledge Management in the new products development of in the kitchen industrial meat, tracing as specific objective: To identify the processes of new products development in the industry; to identify practical of Knowledge Management in the development of new products and To identify the relation enters the Knowledge Management and the development of new products. The considered methodological delineation for this research contemplates the use of qualitative techniques, and is characterized as a case study. For the attainment of the specific data, it was carried out surveys through bibliographical sources and documents of the company, directed comment, as well as questionnaire application. The field research was lead at four distinct moments, in which it was used structuralized questionnaires for data collection, where 136 employees and 06 leaders and managers of the Industrial Unit of Aves and 16 employees and 06 leaders of managers of the Industrial Unit of Carnes, had supplied the information. It was possible to identified that the understanding on management of the knowledge, development of new practical products and of management of the knowledge is understood in a strength way bt the managers, the collaborators of the operational area have minor participation and domain on these questions. The process of development of new products is presented in segmented way, where each sector has a broken up participation. The leaders and managers perceive that the Management of the Knowledge has become efficient in the support and application of the productive processes. Excellent also are the challenges that are presented, amongst them, cites the power of the formation process of the human being and technique of the collaborators, mainly of the UIA, the dissemination of the concepts in relation to the Management of the Knowledge and the practical of KM between the collaborators for the incorporation in the processes and the products of the company. It´s possible to perceive that managers and employees can evaluate in a critical way that the practical application of the knowledge management in the productive processes and to verify the results, that refers to the creation of new products to the Management of the Knowledge and KM practice, become strategically for the marketing performance of the sector.